PBET Learning Strategies in Vocational Education: Linking Journalism Education and Digital Business - Amir Rofiudin; Luhur Adi Prasetya; Salsabila Thifal Nabil Haq; Muhammad Aris Ichwanto; Arvendo Mahardika (Universitas Muhammadiyah Mataram, 2025)
Vocational education plays a crucial role in preparing students for the workforce, particularly in journalism and digital business. This study examines the implementation of Project-Based Education and Training (PBET) in an industrial internship (PKL) at PT Kreasi Ngalam Media and evaluates its impact on vocational high school students' competencies using SWOT analysis. Data were collected through a Likert-scale questionnaire to measure students’ perceptions and open-ended questions to gather qualitative insights. The analysis categorized responses into strengths, weaknesses, opportunities, and threats, followed by descriptive statistical analysis to determine the average score for each component. The results show that strengths (2.21) and opportunities (2.16) significantly outweigh weaknesses (1.1) and threats (1.07), indicating PBET’s effectiveness in enhancing students’ industry adaptability and hands-on experience. A strengths-opportunities (SO) score of 4.37 reinforces its potential to develop relevant vocational skills. However, lower scores in weaknesses and threats highlight ongoing challenges, particularly in bridging the gap between school-based theory and industry practices. To address this, the study recommends structured hands-on training, stronger industry mentorship, and improved school-industry collaboration, ensuring that students acquire practical competencies aligned with industry demands. These recommendations are directly based on the SWOT findings, emphasizing the need for real-world application within PBET to optimize vocational education outcomes and prepare students for the digital workforce. Vocational education plays a crucial role in preparing students for the workforce, particularly in journalism and digital business. This study examines the implementation of Project-Based Education and Training (PBET) in an industrial internship (PKL) at PT Kreasi Ngalam Media and evaluates its impact on vocational high school students' competencies using SWOT analysis. Data were collected through a Likert-scale questionnaire to measure students’ perceptions and open-ended questions to gather qualitative insights. The analysis categorized responses into strengths, weaknesses, opportunities, and threats, followed by descriptive statistical analysis to determine the average score for each component. The results show that strengths (2.21) and opportunities (2.16) significantly outweigh weaknesses (1.1) and threats (1.07), indicating PBET’s effectiveness in enhancing students’ industry adaptability and hands-on experience. A strengths-opportunities (SO) score of 4.37 reinforces its potential to develop relevant vocational skills. However, lower scores in weaknesses and threats highlight ongoing challenges, particularly in bridging the gap between school-based theory and industry practices. To address this, the study recommends structured hands-on training, stronger industry mentorship, and improved school-industry collaboration, ensuring that students acquire practical competencies aligned with industry demands. These recommendations are directly based on the SWOT findings, emphasizing the need for real-world application within PBET to optimize vocational education outcomes and prepare students for the digital workforce.